Self-Control Without a “Self”? - Miller, Holly C.; Pattison, Kristina F.; DeWall, C. Nathan; Rayburn-Reeves, Rebecca; Zentall, Thomas R. (Psychological Science, 2010)
Self-control constitutes a fundamental aspect of human nature. Yet there is reason to believe that human and nonhuman self-control processes rely on the same biological mechanism—the availability of glucose in the bloodstream. Two experiments tested this hypothesis by examining the effect of available blood glucose on the ability of dogs to exert self-control. Experiment 1 showed that dogs that were required to exert self-control on an initial task persisted for a shorter time on a subsequent unsolvable task than did dogs that were not previously required to exert self-control. Experiment 2 demonstrated that providing dogs with a boost of glucose eliminated the negative effects of prior exertion of self-control on persistence; this finding parallels a similar effect in humans. These findings provide the first evidence that self-control relies on the same limited energy resource among humans and nonhumans. Our results have broad implications for the study of self-control processes in human and nonhuman species.